LOW-GRADE INFLAMMATION IN MODERN CIVILIZATION DISEASES: A NARRATIVE REVIEW OF MECHANISMS, BIOMARKERS, AND CLINICAL IMPLICATIONS - Mateusz Mierniczek; Maria Mierniczek; Ewa Gloc; Dominika Dmowska; Paweł Zdebski; Aleksandra Bilińska; Kinga Kaczmarska; Kinga Rosołowska; Jarosław Dudek; Aleksandra Mierniczek (International Journal of Innovative Technologies in Social Science, 2025)
Over the last century, the epidemiological landscape has shifted from acute infectious diseases to chronic non-communicable diseases (NCDs), including cardiovascular disease, type 2 diabetes, and neurodegeneration. These pathologies share a common, underlying biological substrate: chronic, low-grade inflammation, which is hypothesized to arise from an evolutionary mismatch between the human genome and the modern anthropogenic environment. This narrative review synthesizes evidence regarding the molecular mechanisms of sterile inflammation, emerging biomarkers, and therapeutic interventions by integrating data from immunology, metabolic medicine, and large-scale clinical trials. The analysis demonstrates that the pathology is driven by triggers such as metabolic surplus and oxidative stress, which activate the NLRP3 inflammasome and NF-κB pathways. This activation leads to reciprocal dysfunction between insulin signaling and endothelial integrity, creating a metabolic-vascular nexus that drives atherosclerosis, while gut dysbiosis and blood-brain barrier disruption extend this inflammation to the central nervous system, promoting neurodegeneration. While high-sensitivity CRP remains the standard biomarker, emerging markers like suPAR and GlycA offer superior stability and prognostic value. Therapeutically, the CANTOS and LoDoCo2 trials have validated the efficacy of targeting specific inflammatory pathways (IL-1β, NLRP3) over broad immunosuppression. Ultimately, low-grade inflammation is identified as the defining physiological signature of the modern age, serving as the "common soil" for multimorbidity. Effective management necessitates the adoption of a Personalized Immunometabolism framework, integrating biomarker-guided pharmacotherapy (e.g., colchicine) with lifestyle interventions that resolve the fundamental evolutionary mismatch, as future progress depends on bridging the gap between prognostic biomarkers and actionable clinical protocols.